Effect of calcium chloride and hydrothermical treatment on enzymatic activity and phenol content of pineapple - Gonçalves, Neide Botrel; Carvalho, Vânia Déa de; Gonçalves, Jorge Ricardo de Almeida (Pesquisa Agropecuaria Brasileira, 2000)
Pineapple (Ananas comosus Mill.) is exposed to injuries caused by low temperature during the refrigerated storage. The post-harvest application of Ca may contribute to reduce a number of physiological disorders. In this work, the influence of the postharvest application of 2% CaCl2 associated with hydrothermical treatment (38oC and 40oC) for 10 and 20 minutes, on the chemical composition (enzymes, phenols), and susceptibility to internal browning of pineapple ’Smooth Cayenne’ fruits was studied. The fruits were stored at 9oC and 90% relative humidity for 15 days. The evaluations were performed seven days after removal of the fruits from the refrigerated conditions. The immersion of the fruits into a 2% CaCl2 solution reduced the index of internal browning and diminished the activities of the enzymes polyphenoloxidase, peroxidase and phenilalanine ammonium lyase, as well as the content of phenolic compounds when associated with the hydrothermic treatment regardless to the immersion period.